Why and when do you look away when trying to remember? Gaze aversion as a marker of the attentional switch to the internal world during memory retrieval - Anaïs Servais; Noémie Préa; Christophe Hurter; Emmanuel J. Barbeau (Acta Psychologica, 2023)
It is common to look away while trying to remember specific information, for example during autobiographical memory retrieval, a behavior referred to as gaze aversion. Given the competition between internal and external attention, gaze aversion is assumed to play a role in visual decoupling, i.e., suppressing environmental distractors during internal tasks. This suggests a link between gaze aversion and the attentional switch from the outside world to a temporary internal mental space that takes place during the initial stage of memory retrieval, but this assumption has never been verified so far. We designed a protocol where 33 participants answered 48 autobiographical questions while their eye movements were recorded with an eye-tracker and a camcorder. Results indicated that gaze aversion occurred early (median 1.09 s) and predominantly during the access phase of memory retrieval—i.e., the moment when the attentional switch is assumed to take place. In addition, gaze aversion lasted a relatively long time (on average 6 s), and was notably decoupled from concurrent head movements. These results support a role of gaze aversion in perceptual decoupling. Gaze aversion was also related to higher retrieval effort and was rare during memories which came spontaneously to mind. This suggests that gaze aversion might be required only when cognitive effort is required to switch the attention toward the internal world to help retrieving hard-to-access memories. Compared to eye vergence, another visual decoupling strategy, the association with the attentional switch seemed specific to gaze aversion. Our results provide for the first time several arguments supporting the hypothesis that gaze aversion is related to the attentional switch from the outside world to memory.